The Role of Chitosan as a Possible Agent for Enteric Methane Mitigation in Ruminants - Jiménez Ocampo, Rafael; Valencia Salazar, Sara Stephanie; Pinzón Díaz, Carmen Elisa; Herrera Torres, Esperanza; Aguilar-Pérez, Carlos Fernando; Arango, Jacobo; Ku-Vera, Juan Carlos (MDPI, 2019)
Livestock production is a main source of anthropogenic greenhouse gases (GHG). The main gases are CH4 with a global warming potential (GWP) 25 times and nitrous oxide (N2O) with a GWP 298 times, that of carbon dioxide (CO2) arising from enteric fermentation or from manure management, respectively. In fact, CH4 is the second most important GHG emitted globally. This current scenario has increased the concerns about global warming and encouraged the development of intensive research on different natural compounds to be used as feed additives in ruminant rations and modify the rumen ecosystem, fermentation pattern, and mitigate enteric CH4. The compounds most studied are the secondary metabolites of plants, which include a vast array of chemical substances like polyphenols and saponins that are present in plant tissues of different species, but the results are not consistent, and the extraction cost has constrained their utilization in practical animal feeding. Other new compounds of interest include polysaccharide biopolymers such as chitosan, mainly obtained as a marine co-product. As with other compounds, the effect of chitosan on the rumen microbial population depends on the source, purity, dose, process of extraction, and storage. In addition, it is important to identify compounds without adverse effects on rumen fermentation. The present review is aimed at providing information about chitosan for dietary manipulation to be considered for future studies to mitigate enteric methane and reduce the environmental impact of GHGs arising from livestock production systems. Chitosan is a promising agent with methane mitigating effects, but further research is required with in vivo models to establish effective daily doses without any detrimental effect to the animal and consider its addition in practical rations as well as the economic cost of methane mitigation.